Penggunaan Geotextile Sebagai Perkuatan Pada Silinder Beton Mutu Normal - Febrialdo Pratama Salinding; Jonie Tanijaya; Benny Kusuma (Paulus Civil Engineering Journal, 2021)
Because of the transformation of the load of an arrangement on the building infrastructure can receive the load outside the original plan, for that it is necessary to strengthen the structure so that the structure of the building remains safe. In this study the use of woven &non-woven fibers in new concrete is expected to increase strong press, strong tensile and modulus elasticity to conventional concrete. The mix design of the study uses the American Concrete Institute (ACI) method. The test sample of 36 was then divided into 3 variations. The results of this study have shown the addition of strong press, strong pull, and modulus elasticity. Strong press for woven increased 29.485% % and non-woven increased 7.296%, strong pull for woven increased 24.633% and non-woven increased 5.285%., modulus elasticity for woven increased 20,924% and non-woven increased 9.356%. For the comparison of both materials, woven is stronger than non-woven.